Kontribusi Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) Pada Pendapatan Asli Daerah Kabupaten Bengkalis Tahun 2015 – 2019 - Rosmida Rosmida; Julaidah Julaidah (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
Land and Building Tax in Rural and Urban Areas (PBB-P2) is part of the regional tax, has an important role and is a new potential for the receipt of Local Revenue (PAD). This study aims to determine the acceptance of PBB-P2 in Bengkalis Regency, the factors causing the PBB-P2 target in Bengkalis Regency. This research was conducted at the Bapenda Bengkalis Regency office. The object of this research is the report on the receipt of PBB-P2 in Bengkalis Regency from 2015 to 2019. This type of research used is qualitative research using descriptive qualitative methods. Based on the research results the Bengkalis Regency PBB-P2 acceptance within 5 years in general the Bengkalis Regency PBB-P2 revenue never reached the target set by the Bengkalis Regency Government. The cause of not achieving the PBB-P2 target Bengkalis Regency are the lack of understanding and awareness of taxpayers of the important of the role of taxes for regional development, mistakes of the tax apparatus in entering taxpayers data at SPPT, unstable income level of taxpayers, and lack of concrete evidence of taxes paid in improving people’s welfare. Keywords: Tax, PBB-P2, PAD, Bengkalis.